(untitled) (Western European Journal of Historical Events and Social Science, 2024)
This article widely covers the socio-philosophical factors in the formation of respect and loyalty to the national and universal values of the younger generation in the context of the modern process of globalization. In this process, the role and importance of representatives of the older generation was analyzed.